BRCA mutations in women with inflammatory breast cancer. Issue 3 (17th October 2017) - Gutierrez Barrera, Angelica M.; Fouad, Tamer M.; Song, Juhee; Webster, Rachel; Elsayegh, Nisreen; Wood, Anita L.; Demir, Atakan; Litton, Jennifer K.; Ueno, Naoto T.; Arun, Banu K.
Abstract : BACKGROUND: Inflammatory breast cancer (IBC) often affects women at a relatively young age. To the authors' knowledge, the rate of BRCA variants among patients with IBC is not known. To determine the association between BRCA status and IBC, the authors evaluated its rate and compared the clinicopathologic characteristics of patients with IBC with those of patients with other breast cancers (non‐IBC). METHODS: Patients who presented at the study institution's cancer genetics program and who underwent BRCA genetic testing were included in the current study. The authors compared clinicopathologic data between patients with IBC and those with non‐IBC using propensity score matching to identify predictors. RESULTS: A total of 1789 patients who underwent BRCA genetic testing (1684 with non‐IBC and 105 with IBC) were included. BRCA pathogenic variants were found in 27.3% of patients with non‐IBC and 18.1% of patients with IBC ( P  = .0384). After propensity score matching, there were no significant differences noted between patients with IBC and those with non‐IBC, including the rate of BRCA pathogenic variants ( P  = .5485). However, a subgroup analysis of the 479 patients with BRCA pathogenic variants demonstrated that patients with IBC (19 patients) were diagnosed at significantly younger ages compared with patients with non‐IBC ( P  = .0244). CONCLUSIONS: There was no clear association observed between BRCA pathogenic variants and IBC. However, among patients who tested positive for BRCA pathogenic variants, those with IBC were younger at the time of diagnosis compared with those with non‐IBC breast cancers. These results confirm that genetic testing is important for patients with IBC who meet the current clinical criteria for genetic testing in breast cancer. Cancer 2018;124:466‐74. © 2017 American Cancer Society . Abstract : To the authors' knowledge, the current study is the first to uniquely describe the rate of BRCA pathogenic variants among patients with inflammatory breast cancer. The results suggest that the role played by BRCA mutations in the development of inflammatory breast cancer may be similar to their role in other types of breast cancer.